Q-switched pulse operation in erbium-doped fiber laser subject to zirconia (ZrO2) nanoparticles-based saturable absorber - Khalid, Umer Sayyab; Asghar, Haroon; Hameed, Hafsa; Sohail, Muhammad; Khalil, Adnan; Ahmed, Rizwan; Umar, Zeshan A.; Iqbal, Javed; Baig, M. Aslam (Heliyon, 2024)
In this paper, the zirconia (ZrO2) nanoparticles-based saturable-absorber (SA) have been incorporated in an erbium-doped fiber laser (EDFL) cavity for achieving a Q-switched pulse operation. The implementation of the zirconia nanoparticles-based powder on the fiber facet was accomplished using the index-matching gel's adhesion effect. The incorporation of SA in the laser cavity yielded a stable and self-starting Q-switched operation under 19.36 mW pump power that corresponded to the emission wavelength of 1557.29 nm. Additionally, it was observed that the EDFL's emission wavelength tuned from 1557.29 nm to 1562.3 nm , and the repetition rates and pulse width ranged from 61.2 to 130 kHz and 7.9 to 3.6 μs, respectively, as the pump power was increased from 19.36 to 380.16 mW. Measured experimental results reveal that at a maximum pump power of 380.16 mW, the maximum average output power, peak power, and pulse energy were noticed to be 1.17 mW, 2.5 mW, and 9 nJ, respectively. A 52 dB suppression in side bands was found at a pump power of 380.16 mW. Moreover, the stability and threshold tolerance of the EDFL has also been discussed in detail. These findings suggest that nanoparticle-based saturable absorbers have potential applications in a pulsed source, making it easier to implement in fiber cavity-based systems.